Difficulties encountered by grade six pupils in interpreting word problems on elementary mathematics - Platon, Eufrosina Peñaflor 1950- (1977)
The objective of the study was to analyze the difficulties encountered by grade six pupils in interpreting word problems. The instrument used in the study was diagnostic in nature. Results of the study pointed out that the pupils tested are generally weak in interpreting word problems, compounded by the language problem, reading skills, reading comprehension, and failure to do some reflective thinking.
Vita.
Thesis (M.A. Mathematics Education)--University of the Philippines, Diliman.
Keywords: Mathematics -- Study and teaching (Elementary) -- Philippines -- Sipocot (Camarines Sur).; Word problems (Mathematics).; Mathematical ability in children